Identifikasi Senyawa Fitokimia dalam Minyak Pala Fakfak (Myristica argentea Warb) secara Kualitatif - Suloi, Andi Fitra; Nurmiati, Nurmiati; Djurumudi J, Khairunnisa Noervaqriani; Kalista, Ayu (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2025)
Papuan nutmeg (Myristica argentea Warb.) is distributed from the Papua Peninsula to Papua New Guinea. This species is a native and endemic plant of Papua, with a wide distribution in West Papua, particularly in Fakfak Regency. Compared to Banda nutmeg oil, Papuan nutmeg oil contains higher levels of terpineol and safrole, indicating its high potential for further development. Phytochemical compound identification is conducted to provide insight into the potential uses of the bioactive components found in nutmeg seeds, with the aim of optimizing their applications. This study aims to identify the phytochemical compounds present in Fakfak nutmeg oil and to determine its yield. The identification process was carried out qualitatively by reacting the nutmeg oil with specific chemical reagents that correspond to the target compounds. The oil was extracted using the steam distillation method with water as the solvent. The resulting oil yield was 2%, calculated using the decimalization method. Phytochemical screening revealed that the nutmeg oil tested positive for flavonoids, indicated by an orange color change; saponins, indicated by foam formation; and polyphenols, indicated by a green color change. In contrast, tannins were not detected in the sample.